Management of Capitation Funds for First Level Health Facilities Owned by Local Governments - Ario Trisaksono; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
BPJS Kesehatan since operating on January 1, 2014, has collaborated with FKTP to provide services to Participants. Financing for FKTPs that provide health services is done by paying capitation for a number of registered participants. Capitation payments to FKTPs cause problems where the remaining Capitation funds are not absorbed because the utilization of Operational funds from Capitation is not optimal. This has resulted in a relatively large SilPa of Capitation funds in FKTP based on the results of audits conducted by BPK and BPKP.The type of information collection and analysis carried out is descriptive with a qualitative approach. Information gathering is carried out on the provisions of the regulations that have been stipulated and the impact of the implementation of these regulations, as well as opinions that developed in the community and then draw conclusions and deepen the facts.Several regulations that have been stipulated in the utilization of Capitation funds cannot be said to be optimal because they leave problems related to the utilization of Capitation Operational funds which always lead to SilPa. With the enactment of Presidential Regulation 46 of 2021 and Regulation of the Minister of Home Affairs 28 of 2021, it provides a legal basis for BPJS Health to utilize the SilPa of Capitation funds in FKTP for Capitation payments for the current month.It is hoped that with the improvement of existing regulations and the change of FKTP to BLUD, FKTP will give authority to maximize the use of Capitation funds for the provision of infrastructure, medicine and improve the quality of health services to the community.